2002
DOI: 10.1016/s0043-1354(02)00115-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced coagulation using a magnetic ion exchange resin

Abstract: The objective of this investigation was to examine the effectiveness of a magnetic ion exchange resin (MIEX s ) to enhance the coagulation of disinfection by-product precursors in nine surface waters, each representing a different element of the USEPA's 3 Â 3 enhanced coagulation matrix. The effect of MIEX-pretreatment on the requisite alum dose needed for subsequent coagulation of turbidity was also evaluated.Enhanced coagulation with MIEX was found to be very effective for removing trihalomethane (THM) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(133 citation statements)
references
References 21 publications
8
109
1
1
Order By: Relevance
“…Singer and Bilyk analyzed the water quality of nine different water utilities across the United States, and it was found that the TOC concentrations ranged from 2.6 to 26.4 mg/L, the UV absorbance ranged from 0.030 to 1.096 cm − 1 , while the SUVA ranged from 1.4 to 4.5 L/(mg ⋅ m) [79]. Other studies indicated that typical NOM concentration in lake and river waters is ∼0.4-4.0 mg C/L and 10-30 mg C/L for wetlands (which is equivalent to ∼ 0.8-8.0 and 20-60 mg C/L total NOM concentration assuming 50 wt % carbon), and the NOM concentration is typically 1 mg C/L in seawater [77,80].…”
Section: Biocolloid Geocolloid and Natural Organic Mattermentioning
confidence: 99%
“…Singer and Bilyk analyzed the water quality of nine different water utilities across the United States, and it was found that the TOC concentrations ranged from 2.6 to 26.4 mg/L, the UV absorbance ranged from 0.030 to 1.096 cm − 1 , while the SUVA ranged from 1.4 to 4.5 L/(mg ⋅ m) [79]. Other studies indicated that typical NOM concentration in lake and river waters is ∼0.4-4.0 mg C/L and 10-30 mg C/L for wetlands (which is equivalent to ∼ 0.8-8.0 and 20-60 mg C/L total NOM concentration assuming 50 wt % carbon), and the NOM concentration is typically 1 mg C/L in seawater [77,80].…”
Section: Biocolloid Geocolloid and Natural Organic Mattermentioning
confidence: 99%
“…This value was 24% higher than when FeCl 3 was used as coagulant [7]. Other authors found that the coagulation process can reduce haloacetic acid formation potential by 15%-78% [28]. Zhao et al [27] 2013, indicated in their research that the reduction in THMFP and HAAFP by PACl under enhanced coagulation could reach 51% and 59%, respectively, and the removal performance for HAA precursors by PACl was better than when Al 2 (SO 4 ) 3 was used.…”
Section: Methodsmentioning
confidence: 88%
“…Ion exchange resins are very proficient at removing humic substances from water supplies as a large fraction of NOM can be characterised as anionic polyelectrolytes [30]. Previous research on the application of MIEX resin for organic matter control has shown that most dissolved organic matter and UV 254 removal occurs in the first 15-30 min [31][32][33]. It was found 30 min of mixing allows easily removable hydrophobic and hydrophilic NOM to exchange with chloride ion without allowing significant interparticle adsorption of NOM on the resin to occur.…”
Section: Removal Of Ha With Different Al-based Coagulants/miex Resinmentioning
confidence: 99%